Circulating miRNA 887 is differentially expressed in ARDS and modulates endothelial function - Goodwin, Andrew J. (Am J Physiol Lung Cell Mol Physiol, 2020)
Circulating microRNAs (miRNAs) can be taken up by recipient cells and have been recently associated with the acute respiratory distress syndrome (ARDS). Their role in host predisposition to the syndrome is unknown. The objective of the study was to identify circulating miRNAs associated with the development of sepsis-related ARDS and examine their impact on endothelial cell gene expression and function. We determined miRNA levels in plasma collected from subjects during the first 24 h of admission to a tertiary intensive care unit for sepsis. A miRNA that was differentially expressed between subjects who did and did not develop ARDS was identified and was transfected into human pulmonary microvascular endothelial cells (HPMECs). RNA sequencing, in silico analysis, cytokine expression, and leukocyte migration assays were used to determine the impact of this miRNA on gene expression and cell function. In two cohorts, circulating miR-887-3p levels were elevated in septic patients who developed ARDS compared with those who did not. Transfection of miR-887-3p into HPMECs altered gene expression, including the upregulation of several genes previously associated with ARDS (e.g., CXCL10, CCL5, CX3CL1, VCAM1, CASP1, IL1B, IFNB, and TLR2), and activation of cellular pathways relevant to the response to infection. Functionally, miR-887-3p increased the endothelial release of chemokines and facilitated trans-endothelial leukocyte migration. Circulating miR-887-3p is associated with ARDS in critically ill patients with sepsis. In vitro, miR-887-3p regulates the expression of genes relevant to ARDS and neutrophil tracking. This miRNA may contribute to ARDS pathogenesis and could represent a novel therapeutic target.